Rekonstruksi Narasi Cerita Rakyat Melalui Lensa Transformative Learning: Menumbuhkan Agensi Kritis Siswa Sekolah Dasar Generasi Alpha - I Gede Tilem Pastika; Sugita, I Wayan (Adi Widya: Jurnal Pendidikan Dasar, 2025)
Elementary education confronts the epistemological dissonance between the dogmatic content of traditional folklore and the critical characteristics of Generation Alpha students. This research aims to formulate a conceptual framework for narrative reconstruction to align the transmission of cultural values with the psychological needs of modern students. Using a qualitative research design of literature studies with a critical hermeneutic approach, this study operationalizes Jack Mezirow's Transformative Learning Theory. The results of the study offer a mechanism for transforming literary learning through four stages: questioning the moral paradox of stories, analyzing gender/feudalism biases, validating logical ideas, and rewriting narratives. This model transforms students' positions from passive consumers to agents who revitalize culture and effectively foster critical reasoning and empathy aligned with the dimensions of the Graduate Profile in the Independent Learning Curriculum.